Steady and Transient CFD Analysis of a Vertical Axis Ocean Current Turbine - Rasgianti; Agus Suprianto; Ariyana D. Nugraha; Teguh Muttaqie; Ristiyanto Adiputra (Ital Publication, 2026)
Vertical-axis turbines (VATs) are a promising hydrokinetic technology for harvesting renewable energy from ocean currents. Still, their performance depends strongly on design parameters and flow interaction at different azimuthal angles. This study evaluates the performance of a VAT using computational fluid dynamics (CFD) simulations carried out under both steady-state and transient flow conditions. ANSYS CFX is used in the steady-state analysis to estimate torque and power output at various flow velocities and rotational speeds (RPM). At the same time, ANSYS Fluent is applied in the transient analysis to examine time-dependent torque behavior and azimuthal effects under unsteady flow. The steady-state results show that torque and power increase with higher flow velocity and rotational speed, reaching maximum values of 37,079 Nm and 291.86 kW at 4 m/s and 40 RPM. The transient results indicate periodic torque oscillations that become more stable at higher flow velocities, with peak turbine efficiency at 3 m/s, followed by a decrease at 4 m/s due to possible hydrodynamic losses. These findings provide clearer insight into VAT performance under realistic operating conditions and may support future efforts to improve hydrokinetic turbine design.